2015
DOI: 10.1371/journal.ppat.1005261
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of a Neuroinvasive Human Respiratory Virus Spike Glycoprotein by Proprotein Convertases Modulates Neurovirulence and Virus Spread within the Central Nervous System

Abstract: Human coronaviruses (HCoV) are respiratory pathogens that may be associated with the development of neurological diseases, in view of their neuroinvasive and neurotropic properties. The viral spike (S) glycoprotein is a major virulence factor for several coronavirus species, including the OC43 strain of HCoV (HCoV-OC43). In an attempt to study the role of this protein in virus spread within the central nervous system (CNS) and neurovirulence, as well as to identify amino acid residues important for such functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 64 publications
(93 reference statements)
7
95
0
1
Order By: Relevance
“…Functional viroporins and viral PBM are associated with viral pathogenesis for a growing number of viruses and their studies to better understand virus-host interaction represent an emerging field (Javier and Rice, 2011;Nieva et al, 2012;Scott and Griffin, 2015). Considering that the HCoV-OC43 E protein seems to possess both functions and that they seem to be important for the induction of disease, future studies regarding their functionality and underlying mechanisms resulting in HCoV-OC43 neuropathogenesis previously described (Brison et al, 2011;Jacomy et al, 2006;Le Coupanec et al, 2015) are warranted and necessary as they will help to identify virus-host interfaces which could represent therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional viroporins and viral PBM are associated with viral pathogenesis for a growing number of viruses and their studies to better understand virus-host interaction represent an emerging field (Javier and Rice, 2011;Nieva et al, 2012;Scott and Griffin, 2015). Considering that the HCoV-OC43 E protein seems to possess both functions and that they seem to be important for the induction of disease, future studies regarding their functionality and underlying mechanisms resulting in HCoV-OC43 neuropathogenesis previously described (Brison et al, 2011;Jacomy et al, 2006;Le Coupanec et al, 2015) are warranted and necessary as they will help to identify virus-host interfaces which could represent therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…As HCoV-OC43 is naturally neuroinvasive and neurovirulent in mice (Brison et al, 2011;Desforges et al, 2014;Le Coupanec et al, 2015) and that the E protein is important for efficient propagation in neuronal cells (Figs. 3 and 4), we wished to investigate the importance of the two functional domains of E in the process of neuroinvasion.…”
Section: Fully Competent Hcov-oc43 E Protein Is Not Essential For Neumentioning
confidence: 99%
See 2 more Smart Citations
“…They have the potential to cleave specifically viral envelope glycoproteins, thereby enhancing viral fusion with host cell membranes (Izaguirre, 2019;Moulard and Decroly, 2000). In the case of human-infecting coronaviruses such as HCoV-OC43 (Le Coupanec et al, 2015), MERS-CoV (Millet and Whittaker, 2014), and HKU1 (Chan et al, 2008) the spike protein has been demonstrated to be cleaved at an S1/S2 cleavage site (Fig. 2) generating the S1 and S2 subunits.…”
mentioning
confidence: 99%